Fluorinated-functionalized hyaluronic acid nanoparticles for enhanced photodynamic therapy of ocular choroidal melanoma by ameliorating hypoxia. (1st June 2020) - Li, Jipeng; Xue, Yudong; Tian, Jun; Liu, Zeyang; Zhuang, Ai; Gu, Ping; Zhou, Huifang; Zhang, Weian; Fan, Xianqun
Highlights: Synthesis of Ac-HA-PFC-Ppa nanoparticles and show outstanding hydrophilia, biocompatibility and degradability. Good oxygen carrying capacity of Ac-HA-PFC-Ppa nanoparticles to the tumor microenvironment. Enhanced photodynamic therapy effect of ocular choroidal melanoma. Abstract: Photodynamic therapy (PDT) is a method for killing cancer cells by employing reactive singlet oxygen ( 1 O2 ). However, the inherent hypoxia and oxygen consumption in tumors during PDT lead to a deficient oxygen supply, which in turn hinder the photodynamic efficacy. To overcome this issue, fluorinated-functionalized polysaccharide-based nanocomplexes were prepared by anchoring perfluorocarbons (PFCs) and pyropheophorbide a (Ppa) onto the polymer chains of hyaluronic acid (HA) to deliver O2 in hypoxia area. These amphiphilic conjugates can self-assemble into micelles and its application in PDT is evaluated. Due to the high oxygen affinity of perfluorocarbon segments, and the tumor-targeting nature of HA, the photodynamic effect of the oxygen self-carrying micelles is remarkably enhanced, which is confirmed by increased generation of 1 O2 and elevated phototoxicity in vitro and in vivo . These results emphasize the promising potential of polysaccharide-based nanocomplexes for enhanced PDT of Ocular Choroidal Melanoma.